DSFit: a feasibility pilot study of a group exercise programme for adolescents with Down syndrome. Issue 12 (27th September 2022) - Hojlo, M. A.; Milliken, A. L.; Baumer, N. T.; Davidson, E. J.
Abstract: Background: While past research has underscored the benefits of physical activity for people with Down syndrome (DS), exercise programming that is customised to and/or accessible for children and adolescents with DS is limited. The objectives of this pilot were to (1) develop and refine an engaging exercise programme for adolescents with DS, called DSFit; (2) assess feasibility over the course of two pilot iterations; and (3) examine participant and parent feedback regarding exercise priorities and the DSFit exercise programme. Method: Participants were 12 unique adolescents (ages 11–17 years) with DS. Both pilot iterations of the programme consisted of weekly group exercise sessions and home exercises to complete between sessions. Physical fitness and mood/behaviour were assessed at baseline and at the end of the intervention. Parent and child goal‐setting and feedback surveys were collected before and immediately after the intervention, and a 2‐month follow‐up assessed physical activity and exercise attitudes. Quality improvement methodology and participant/parent feedback were used to modify the second iteration to better meet the needs of our study population. Changes included an expanded age range, modified physical assessments, decreased burden of questionnaires, and video‐recorded group sessions for at‐home practice. Results: Physical fitness evaluation of core/trunk strength and stability, lower‐ and upper‐body strength, balance, flexibility, and walking was feasible, and the majority of participants in both pilot iterations improved in at least one category of physical assessment between baseline and end of intervention. Assessment of symptoms of anxiety, depression and behavioural concerns was also feasible and results showed slight improvements in some participants. Both parent and participant feedback indicated that participants enjoyed the programme and appreciated the opportunity to start developing sustainable exercise habits. Conclusions: A group exercise programme with supported at‐home components is feasible for adolescents with DS. Future iterations will continue to examine programme efficacy with improved fitness testing and larger sample sizes. Strategies to increase at‐home compliance, such as virtual sessions and parent/guardian‐guided physical fitness assessments, will also be incorporated.